Efficacy of Hydrotherapy Soak Feet in Lowering Blood Pressure of Hypertension Sufferers in Dauhwaru Village, Jembrana - I Putu Sudiartawan; I Made Dwi Mertha Adnyana (Institute of Computer Science (IOCS), 2022)
Hypertension fluctuates significantly every year, especially in Jembrana Regency. Long-term consumption of the drug may result in complications. This study aims to analyze the efficacy of foot soak hydrotherapy in lowering the blood pressure of hypertension sufferers in Dauhwaru Village, Jembrana. Experimental research design with one group pretest-posttest design without any control group. In 37 respondents with hypertension, the treatment consisted of 20 minutes of hydrotherapy in which the feet were immersed in 25-centimeter-deep water. The data was analyzed using a Paired T-Test and descriptive tests. The results showed that respondents aged 31–40 years (51.4%), male (54.1%), independent entrepreneurial work (40.5%), senior high school graduate education (35.1%), a daily work duration of > 12 hours/day, and respondents who had used anti-hypertensive medications for 6–8 years (37.8%) dominated the age characteristics. Hence, the results obtained from the T-test obtained a probability value (2-tailed) of 0,000 < 0.01. Hence, there is a very noticeable difference in blood pressure before and after being given foot-soak hydrotherapeutic treatment in hypertension patients in Dauhwaru Village, with a lowering in systolic blood pressure of 124.3 mmHg and diastolic blood pressure of 0.62.2 mmHg. Therefore, hydrotherapy soak feet is effective in lowering blood pressure.